Embracing a culture of talk: STEM teachers' engagement in small-group discussions about photovoltaics - Carla M. Firetto; Emily Starrett; Michelle E. Jordan (SpringerOpen, 2023)
Abstract Background Small-group discussions are well established as an effective pedagogical tool to promote student learning in STEM classrooms. However, there are a variety of factors that influence how and to what extent K-12 teachers use small-group discussions in their classrooms, including both their own STEM content knowledge and their perceived ability to facilitate discussions. We designed the present study to specifically target these two factors in the context of photovoltaics, an interdisciplinary field at the intersection of all STEM disciplines with potential to yield widespread benefits related to the use of solar technologies as a sustainable, renewable energy source. Teachers engaged in a series of small-group discussions based on photovoltaic source material (e.g., scientific articles) to build both their STEM content knowledge and capability with discussions, promoting their potential to design and deliver STEM instruction in their own classrooms using small-group discussion. Results Overall, teachers productively engaged in rich STEM talk as they spent most of the time in the discussion asking authentic questions about photovoltaic topics in alignment with a variety of science and engineering disciplinary core ideas, responding to the questions with rich, elaborative talk, and taking on ownership of the discussions. Teachers also evidenced increases in their photovoltaic knowledge and their perceived capability to facilitate discussions. Finally, most teachers' end-of-program lesson plans included the use of small-group discussions, and a subsample of teachers who completed a follow-up interview one year after the summer program reported greater enactment of discussion in their STEM classrooms. Conclusion Our manuscript forwards an important contribution that draws from a practice-based approach to professional development in a way that not only better prepares teachers on what to teach (i.e., through enhanced PV content knowledge), but it also supports their ability to implement this instruction into their classrooms more effectively (i.e., though the use of small-group discussion). As such, this manuscript illustrates an innovative pedagogical approach for potential use in supporting teacher education and informs ways to enable teachers to build enhanced curricula for their STEM students.